Cadmium exposure and risk of pancreatic cancer: Systematic review and meta-analysis - Yaser Soleimani; Mohammad Nayebi; Sheyda Mahmoudi; Mahdi Daraei; Soroush Khorsand; Mohammad amin Jahazi; Maryam Yadollahi Farsi; Fatemeh Khalafi; Mahdieh Varseh; Zahra Mousavi Jarrahi; Mahna Soleimani; Kamelia Massoudnia; et al. (PLoS ONE, 2025)
Background Pancreatic cancer is one of the most lethal malignancies, characterized by a poor prognosis and limited treatment options. Increasing evidence suggests that environmental factors, including heavy metal exposure, play a role in pancreatic cancer development. Cadmium, a toxic heavy metal classified as a Group 1 carcinogen, has been implicated in cancer progression. However, its association with pancreatic cancer remains uncertain, with conflicting results from epidemiological studies. This systematic review and meta-analysis aim to assess the association between cadmium exposure and the risk of pancreatic cancer. Methods A comprehensive literature search was conducted using multiple databases to identify studies that explored the relationship between cadmium exposure and pancreatic cancer risk. Eleven eligible studies were included in the meta-analysis. Pooled odds ratios (OR) with 95% confidence intervals (CI) were calculated to estimate the overall effect size. Heterogeneity was assessed using I², T², and Cochran’s Q-test. Publication bias was evaluated using Egger’s and Begg’s tests. Results The pooled analysis revealed a significant association between cadmium exposure and the risk of pancreatic cancer, with an overall OR of 2.01 (95% CI: 1.30, 2.72), indicating that individuals exposed to cadmium had more than twice the risk of developing pancreatic cancer compared to those with lower or no exposure. Substantial heterogeneity was observed across studies (I² = 98.08%, T² = 1.37, H² = 52.21). Cochran’s Q-test also indicated significant heterogeneity (Q(10) = 304.52, p = 0.00). Egger’s test (p = 0.5040) and Begg’s test (p = 1.0000) showed no evidence of publication bias. Conclusion This meta-analysis demonstrates a significant positive association between cadmium exposure and an increased risk of pancreatic cancer. Despite the considerable heterogeneity across studies, the findings suggest that cadmium is a potential environmental risk factor for pancreatic cancer. Further research is required to explore the underlying biological mechanisms and to develop strategies for reducing cadmium exposure, particularly in high-risk populations.